A Phase-Appropriate Risk Assessment Strategy in Support of the Safety of Peptide and Oligonucleotide-Related Impurities - Brian W. Pack; Robert W. Siegel; Paul D. Cornwell; Andrea Ferrante; Douglas A. Roepke; Michael E. Hodsdon; Laurent Malherbe; Mark A. Carfagna (The AAPS Journal, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

BeyondⓇ extender in donkey semen: evaluation at 5 °C and 17 °C over 7 days - M. Caldevilla; D. Neild; A. Ferrante; I. Cáceres Monie; C. Arraztoa; J. Plaza; J. Otero; M. Gambarotta; M. Miragaya (Journal of Equine Veterinary Science, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Assessing the effects of a commercial fungicide and an herbicide, alone and in combination, on Apis mellifera: Insights from biomarkers and cognitive analysis - Agata Di Noi; Ilaria Caliani; Antonella D'Agostino; Giampiero Cai; Marco Romi; Tommaso Campani; Federico Ferrante; David Baracchi; Silvia Casini (Chemosphere, 2024)

Indoor quality-oriented approach for the performance evaluation of building retrofit with façade transformation: Case study of student dormitory in Mediterranean climate - A. Gigante; D. Papadaki; C. Mazzoli; V. Ntouros; R.F. De Masi; M.-N. Assimakopoulos; Annarita Ferrante (Energy and Buildings, 2024)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

What ecological and functional changes follow the positioning of an artificial barrier? Answers from a 4-year investigation on soft bottom benthic communities - Michela D’Alessandro; Federica Nasi; Larissa Ferrante; Salvatore Giacobbe (Hydrobiologia, 2021)

Human endogenous retroviruses env gene expression and long terminal repeat methylation in colorectal cancer patients - Maria Dolci; Chiara Favero; Letizia Tarantini; Sonia Villani; Marco Bregni; Lucia Signorini; Alberto Della Valle; Filippo Crivelli; Sarah D’Alessandro; Pasquale Ferrante; Valentina Bollati; Serena Delbue (Medical Microbiology and Immunology, 2020)

Biotic and Abiotic Drivers of Topsoil Organic Carbon Concentration in Drylands Have Similar Effects at Regional and Global Scales - Juan J. Gaitán; Fernando T. Maestre; Donaldo E. Bran; Gustavo G. Buono; Andrew J. Dougill; Guillermo García Martínez; Daniela Ferrante; Reginald T. Guuroh; Anja Linstädter; Virginia Massara; Andrew D. Thomas; Gabriel E. Oliva (Ecosystems, 2019)

Characterisation of Pseudomonas syringae isolates from apricot orchards in north-eastern Italy - D. Giovanardi; P. Ferrante; M. Scortichini; E. Stefani (European Journal of Plant Pathology, 2018)

Neuro-Mechanics of Recumbent Leg Cycling in Post-Acute Stroke Patients - Emilia Ambrosini; Cristiano De Marchis; Alessandra Pedrocchi; Giancarlo Ferrigno; Marco Monticone; Maurizio Schmid; Tommaso D’Alessio; Silvia Conforto; Simona Ferrante (Annals of Biomedical Engineering, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Establishment of Genetic Transformation in the Sexually Reproducing Diatoms Pseudo-nitzschia multistriata and Pseudo-nitzschia arenysensis and Inheritance of the Transgene - Valeria Sabatino; Monia Teresa Russo; Shrikant Patil; Giuliana d’Ippolito; Angelo Fontana; Maria Immacolata Ferrante (Marine Biotechnology, 2015)

Insecticidal and anti-microbial activity of bio-oil derived from fast pyrolysis of lignin, cellulose, and hemicellulose - Mohammad M. Hossain; Ian M. Scott; Brian D. McGarvey; Kenneth Conn; Lorenzo Ferrante; Franco Berruti; Cedric Briens (Journal of Pest Science, 2015)

Bioaccumulation of heavy metals in Parablennius sanguinolentus and related biomarkers of exposure. - Camiolo Giuseppina; Puglisi Fabrizio; Pecoraro Roberta; D'Amante Giusi; Droutsa Angeliki; Salvaggio Antonio; Ferrante Margherita; Brundo Maria; Tibullo Daniele; Tiralongo Francesco (Frontiers in Marine Science, 2015)

Effects of Pseudomonas fluorescens Seed Bioinoculation on Heavy Metal Accumulation for Mirabilis jalapa Phytoextraction in Smelter-Contaminated Soil - M. Petriccione; D. Di Patre; P. Ferrante; S. Papa; G. Bartoli; A. Fioretto; M. Scortichini (Water, Air, & Soil Pollution, 2013)

The interactions of age, sex, body mass index, genetics, and steroid weight-based doses on tacrolimus dosing requirement after adult kidney transplantation - P. Stratta; M. Quaglia; T. Cena; R. Antoniotti; R. Fenoglio; A. Menegotto; D. Ferrante; A. Genazzani; S. Terrazzino; C. Magnani (European Journal of Clinical Pharmacology, 2012)

Omega-3 fatty acid supplementation reduces one-year risk of atrial fibrillation in patients hospitalized with myocardial infarction - Alejandro Macchia; Simona Monte; Fabio Pellegrini; Marilena Romero; Daniel Ferrante; Hernán Doval; Antonio D’Ettorre; Aldo Pietro Maggioni; Gianni Tognoni (European Journal of Clinical Pharmacology, 2008)

CNTO 95, a fully human anti αv integrin antibody, inhibits cell signaling, migration, invasion, and spontaneous metastasis of human breast cancer cells - Qiming Chen; Carol D. Manning; Hillary Millar; Francis L. McCabe; Catherine Ferrante; Celia Sharp; Lillian Shahied-Arruda; Parul Doshi; Marian T. Nakada; G. Mark Anderson (Clinical & Experimental Metastasis, 2008)

Persistent Organochlorine Pollutants in Liver of Birds of Different Trophic Levels from Coastal Areas of Campania, Italy - B. Naso; D. Perrone; M. C. Ferrante; A. Zaccaroni; A. Lucisano (Archives of Environmental Contamination and Toxicology, 2003)

Subgrouping of human rotavirus strains by complement fixation, indirect double-antibody sandwich enzyme-linked immunosorbent assay and solid-phase immune electron microscopy - G. Gerna; M. Torsellini; N. Passarani; M. Battaglia; E. Percivalle; A. Sarasini; D. Torre; P. Ferrante (Archives of Virology, 1984)